Pengembangan Soal Setara AKM Numerasi Domain Aljabar untuk Siswa Sekolah Menengah Pertama - Wijaya, Muhammad Avicenna Wahyu; Khabibah, Siti (Universitas Negeri Surabaya, 2025)
This research uses the Tessmer (1995) development model which aims to describe the process of developing questions equivalent to AKM numeracy in the junior high school algebra domain and produce valid and reliable questions. The research instruments used include question validation sheets and student evaluation sheets. At the preliminary stage, the researcher reviewed the literature, contacted schools, determined the domain to be developed, determined the question items, and designed the questions. At stage self evaluation, The questions designed are evaluated by peers and produce results prototype 1. At the level of expert review, The assessment of 3 experts showed that the 16 questions developed were valid in terms of material, construction and language aspects. At stage one-to-one, prototype 1 tested on 3 students with moderate mathematical abilities to review the language of each question. At the small group stage, Prototype 2 tested on 6 students to review the duration of the work and found that the work duration was 80 minutes. At stage field test, prototype 3 tested on 30 students to collect data to test the validity and reliability of the question items. This research resulted in 14 valid and reliable items that can be used to assess student competencies and as practice questions for facing numeracy assessments in the AKM.